Paepalanthus modestus (Eriocaulaceae), a new dimerous species from Goias, Brazil, with notes on leaf and scape anatomy - Trovo, Marcelo; Silva, Arthur de Lima [UNESP]; Coan, Alessandra Ike [UNESP] (Magnolia Press, 2017)
Paepalanthus modestus, a new species of Eriocaulaceae with dimerous flowers, is described and illustrated. The species is placed in P. [unranked] Dimeri based on floral and vegetative characters. A detailed comparison with P. harleyi and P. oxyphyllus is given. The hemispherical mature capitula, the relatively short involucral bracts slightly surpassing the floral disc, and the vestiture of leaves, scapes, and floral parts distinguish P. modestus. Large populations of the species occur on rocky soils in the municipalities of Alto Paraiso de Goias and Teresina de Goias, Brazil. Some of these populations were found in Chapada dos Veadeiros National Park, and the species is considered endangered according to the IUCN criteria. Anatomical details of leaves and scapes, along with photos and comments on etymology, morphological variation, and ecological aspects related to fire tolerance are provided.
Keywords: Central Brazil; Poales; Paepalanthoideae; Taxonomy; Endemism